2016
DOI: 10.1002/chem.201602171
|View full text |Cite
|
Sign up to set email alerts
|

Small Cation‐Based High‐Performance Energetic Nitraminofurazanates

Abstract: Large nitramino-substituted furazan anions were combined with small cations (hydroxylammonium, hydrazinium, and ammonium) to form a series of energetic salts that was fully characterized. The structures of several of the compounds (1 a, 2 a, 3 a, and 4 a) were further confirmed by single-crystal X-ray diffraction. Based on their physiochemical properties, such as density, thermal stability, and sensitivity, together with the calculated detonation properties, it was found that they exhibit good detonation perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…By incorporating energy-rich functional groups (-NO 2 , -NHNO 2 , -ONO 2 , etc.) into furazan backbones, a large number of energetic materials with excellent detonation properties were successfully developed (Tang et al, 2016;Liu et al, 2018;Zhai et al, 2019;Zhang et al, 2019). Meanwhile, it is noteworthy that an inevitable and inherent contradiction existed SCHEME 1 | (A-C) Electrostatic potential of compounds 6 and 8 [B3LYP/6-31+G** 0.001 electron/b3 isosurface, energy values −0.03 to +0.03 H].…”
Section: Introductionmentioning
confidence: 99%
“…By incorporating energy-rich functional groups (-NO 2 , -NHNO 2 , -ONO 2 , etc.) into furazan backbones, a large number of energetic materials with excellent detonation properties were successfully developed (Tang et al, 2016;Liu et al, 2018;Zhai et al, 2019;Zhang et al, 2019). Meanwhile, it is noteworthy that an inevitable and inherent contradiction existed SCHEME 1 | (A-C) Electrostatic potential of compounds 6 and 8 [B3LYP/6-31+G** 0.001 electron/b3 isosurface, energy values −0.03 to +0.03 H].…”
Section: Introductionmentioning
confidence: 99%
“…This result well matches to the previous report in which the combination of a large anion and small cation could form high-density energetic compounds. 37 Unlike most of the cations from ammonium to imidazolium ions, which were generally well distributed along the correlation line (dashed), the Dv values for hydrazinium groups (navy triangle) deviated from the correlation line (Fig. 4c).…”
Section: Structural Analysismentioning
confidence: 92%
“…It has been reported that hydrazinium ions pertain lower electrostatic potential (ESP), which is a critical clue in intermolecular interactions. 37 In particular, the deviation was larger when two hydrazinium ions were combined in an anion (cpd 307). Nonetheless, the hydrazinium group showed a higher Dv than guanidinium ions (Dv < 9,200 m/s).…”
Section: Structural Analysismentioning
confidence: 99%
“…More importantly, the combination of azoles with various energetic groups like amino, nitro, nitramino, azido, and polynitromethyl could produce a considerable variety of energetic materials, which have diverse properties and meet different demands of application. Compared with single heterocyclic structures, C–C bonded bisheterocyclic, , triheterocyclic, and even tetraheterocyclic compounds usually have a higher heat of formation, good sensitivity, and better thermal stability derived from larger π-conjugated systems. Typical examples for these kinds of compounds are illustrated in Figure .…”
Section: Introductionmentioning
confidence: 99%